THE CURRENT STATE OF TAXATION AND ITS IMPACT ON THE FINANCIAL RESULTS BRANCHES OF "BILA TSERKVA FORESTRY" SSEE "FORESTS OF UKRAINE" - Хрик, Василь; Кімейчук, Іван; Ситник, Олександр; Левандовська, Світлана (SWorldJournal, 2024)
The article calculates the state of taxation and its impact on the financial results of the "Bila Tserkva Forestry" branch of the State Enterprise "Forests of Ukraine". The main indicators of taxation are determined, including: income tax, value added tax